The ways of using Modern Merthods and Technologies in Russian Language Lessons - Kazimova, Gulnora Hakimovna (European Journal of Life Safety and Stability (2660-9630), 2022)
The article contains theoretical information about new technologies that can be used in the lessons of the Russian language and literature in order to draw the attention of schoolchildren to the material being studied, to intensify their independent work in the classroom, and to increase interest in the subject.